Differential expression of CARMIL‐family genes during zebrafish development. Issue 10 (23rd October 2015) - Stark, Benjamin C.; Cooper, John A.
Abstract : CARMILs are a conserved family of large multidomain proteins that regulate and target actin assembly by interacting with actin capping protein (CP). Vertebrates contain three highly conserved CARMIL isoforms encoded by three genes, whereas lower organisms contain only one isoform and gene. In order to investigate the functions of vertebrate CARMILs, we identified and characterized the three CARMIL genes in zebrafish ( Danio rerio ). We isolated and sequenced complete and partial cDNAs from embryos. The three genes display distinct spatial and temporal expression patterns during development. Sequence and phylogenetic analyses of cDNAs and predicted protein sequences reveal that the three zebrafish genes fall into the three conserved isoform groups previously defined for other vertebrates, which have isoform‐specific and overlapping functions in human cultured cells. These results provide new tools and offer insight into understanding the role of the regulation of actin assembly dynamics during embryonic development and tissue morphogenesis. © 2015 Wiley Periodicals, Inc.